PENGARUH PENDEKATAN REALISTIC MATHEMATICS EDUCATION TERHADAP PENALARAN MATEMATIS: SYSTEMATIC LITERATUR REVIEW - Chelsi Ariati; Dadang Juandi (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
The purpose of this study was to determine whether the Realistic Mathematics Education Approach had an effect on students' mathematical reasoning abilities. The method used in this research is Systematic Literature Review. The search strategy was adapted to the selection criteria and used the PRISMA protocol as a guide for the research instrument. The data analysis technique used is data grouping, data analysis and data inference. The results of the study show: (1) There is an effect of the Realistic Mathematics Education (RME) Approach on students' reasoning abilities. (2) The Realistic Mathematics Education approach is an alternative solution for teachers to develop students' reasoning abilities. (3) Technologies that can be used in learning mathematics to improve reasoning abilities are Geogrebra, Computer Game (Snake and Ladder), and Powerpoint. (4) There is heterogeneity in research on the effect of Realistic Mathematics Education Approach on students' reasoning abilities, for example, year of publication, level of education, sample size, status of technology assistance and materials used in research.